Adaptive Reasoning Characteristics of Vocational School Students in Solving Mathematic Problems - Dian Septi Nur Afifah; Mohammad Syauqy; Muhammad Ilman Nafian (AL-ISHLAH: Jurnal Pendidikan, 2023)
The primary objective of this study was to provide a comprehensive description of the adaptive thinking attributes exhibited by students enrolled in vocational high schools when engaged in the process of solving mathematical problems. The present study is characterised as a qualitative descriptive investigation. The research employed mathematical test questions and interview guides as the primary instruments. The data collection methods employed in this study encompass both tests and interviews. Data analysis includes the processes of data reduction, data display, and the derivation of conclusions. Checking the validity of the data was carried out by triangulating the source and the adequacy of the reference data. This research was conducted on XI-grade students of SMK X in the vocational field of Motorcycle Engineering (TSM). There are three subjects in this study, they are students who can solve the problem correctly. Based on the results of data analysis, it is concluded that adaptive reasoning characteristics of TSM students in solving math problems and making plans are using different strategies as alternative answers, in providing an allegation of problem-solving, namely by assuming an example in the form of writing and pictures to solve the problem. In the completion stage, students solve problems by linking previous knowledge. In making conclusions, TSM students are simpler and get to the heart of the problem.